A Multicenter Consortium to Define the Epidemiology and Outcomes of Inpatient Respiratory Viral Infections in Pediatric Hematopoietic Stem Cell Transplant Recipients. (1st July 2017) - Fisher, Brian T; Danziger-Isakov, Lara; Sweet, Leigh R; Munoz, Flor M; Maron, Gabriela; Tuomanen, Elaine; Murray, Alistair; Englund, Janet A; Dulek, Daniel; Halasa, Natasha; Green, Michael; Michaels, Marian G; et al.
Abstract: Background: Respiratory virus infections (RVIs) pose a threat to children undergoing hematopoietic stem cell transplantation (HSCT). In this era of sensitive molecular diagnostics, the incidence and outcome of HSCT recipients who are hospitalized with RVI (H-RVI) are not well described. Methods: A retrospective observational cohort of pediatric HSCT recipients (between January 2010 and June 2013) was assembled from 9 US pediatric transplant centers. Their medical charts were reviewed for H-RVI events within 1 year after their transplant. An H-RVI diagnosis required respiratory signs or symptoms plus viral detection (human rhinovirus/enterovirus, human metapneumovirus, influenza, parainfluenza, coronaviruses, and/or respiratory syncytial virus). The incidence of H-RVI was calculated, and the association of baseline HSCT factors with subsequent pulmonary complications and death was assessed. Results: Among 1560 HSCT recipients, 259 (16.6%) acquired at least 1 H-RVI within 1 year after their transplant. The median age of the patients with an H-RVI was lower than that of patients without an H-RVI (4.8 vs 7.1 years; P < .001). Among the patients with a first H-RVI, 48% required some respiratory support, and 14% suffered significant pulmonary sequelae. The all-cause and attributable case-fatality rates within 3 months of H-RVI onset were 11% and 5.4%, respectively. Multivariate logistic regression revealed that H-RVI onset within 60 days of HSCT, steroid use in the 7 days before H-RVI onset, and the need for respiratory support at H-RVI onset were associated with subsequent morbidity or death. Conclusion: Results of this multicenter cohort study suggest that H-RVIs are relatively common in pediatric HSCT recipients and contribute to significant morbidity and death. These data should help inform interventional studies specific to each viral pathogen.